Kompetensi Sosial Guru Pendidikan Agama Islam dalam Meningkatkan Prestasi Siswa - Parnawi, Afi (FENOMENA, 2018)
As a proffesional person in the field of education, teacher has some roles, such as: being a teacher, mentor, class adminisrator, curriculum developer, profiessionla developer, and public relation. A competence, in the perspective of education, is a necessity, since it must be based on the mastery of a knowledge. The teacher’s social competence should be the tools of communcation and interaction to the students, fellow educators, educational officers, students’ parents, and the society. Education has an important role in improving the quality of human resources and as an efforts to realize the public welfare of the intelectual life of the nation. Taken from the decree of Indonesian government, it is stated that “Education is implemented to develop the capabilities and to shape the dignified national character aiming to develop the potetentials of Indonesian people to be faithful and devoted to Allah and to create the  noble, healthy, knowledgable, capable, crative, and independent person as well as to become a democratic and responsible citizen.